ANALISIS EFEKTIVITAS PENGGUNAAN ALAT BERAT PADA SUATU PROYEK KONSTRUKSI (Studi Kasus : Pembangunan Kolam Retensi Wilayah Sirnaraga – Kota Bandung) - Syapril Janizar; Aldy Ardianto; Felix Setiawan (Departement of Civil Engineering, Universitas Winaya Mukti, 2023)
This research is motivated by the need to observe and analyze the efficiency of using heavy equipment in the retention pond construction project in the Sirnaraga area. The purpose of this study was to determine the production capacity of heavy equipment used, the efficiency factor of heavy equipment and to analyze the effect of the efficiency factor on the production capacity of heavy equipment. The method used in this research is descriptive analytic method which focuses on solving actual problems, where the data collected, compiled, explained and analyzed. The results showed that the production capacity of heavy equipment for excavators was 52.14 m3/hour, dump truck was 11.60 m3/hour, stamper was 540.00 m3/hour, vibrator concrete was 750 m3/hour, portable concrete mixer pump was 83 m3/hour, and hydraulic truck crane of 10.384 tons/hour; efficiency factor of heavy equipment for excavator is 0.83 (good operating condition), dump truck is 0.80 (medium), stamper is 0.81 (good), vibrator concrete is 0.83 (good), portable concrete mixer pump is 0.83 (good), and hydraulic truck crane 0.83 (good); The greater the production capacity of each unit of heavy equipment, the higher the efficiency factor of the heavy equipment obtained with good operating conditions. Vice versa, if the production capacity is small, the efficiency factor value of the heavy equipment used will also be small.